Exogenous Angiotensin I Metabolism in Aorta Isolated from Streptozotocin Treated Diabetic Rats. (10th October 2016) - Wołkow, P. P.; Bujak-Giżycka, B.; Jawień, J.; Olszanecki, R.; Madej, J.; Rutowski, J.; Korbut, R.
Abstract : Purpose . Products of angiotensin (ANG) I metabolism may predispose to vascular complications of diabetes mellitus. Methods . Diabetes was induced with streptozotocin (75 mg/kg i.p.). Rat aorta fragments, isolated 4 weeks later, were pretreated with perindoprilat (3  μ M), thiorphan (3  μ M), or vehicle and incubated for 15 minutes with ANG I (1 μ M). Products of ANG I metabolism through classical (ANG II, ANG III, and ANG IV) and alternative (ANG (1–9), ANG (1–7), and ANG (1–5)) pathways were measured in the buffer, using liquid chromatography-mass spectrometry. Results . Incubation with ANG I resulted in higher concentration of ANG II ( P = 0.02, vehicle pretreatment) and lower of ANG (1–9) (P = 0.048, perindoprilat pretreatment) in diabetes. Preference for the classical pathway is suggested by higher ANG III/ANG (1–7) ratios in vehicle (P = 0.03 ), perindoprilat (P = 0.02 ), and thiorphan pretreated (P = 0.02 ) diabetic rat. Within the classical pathway, ratios of ANG IV/ANG II (P = 0.01 ) and of ANG IV/ANG III (P = 0.049 ), but not of ANG III/ANG II are lower in diabetes. Conclusions . Diabetes in rats led to preference toward deleterious (ANG II, ANG III) over protective (ANG IV, ANG (1–9), and ANG (1–7)) ANG I metabolites.